Optimalisasi Metode Pembiasaan 5 Kata Ajaib Dalam Membentuk Karakter Santun Pada Anak Usia 4-6 Tahun - Nur Hijriyati Waisa lilis; Masganti Sitorus (Universitas Muhammadiyah Metro, 2026)
This study was motivated by a lack of polite behavior among children aged 4–6 years, evidenced by infrequent use of polite language, inadequate social interaction skills, a lack of concern for peers, and insufficient responsibility in daily activities. The study aimed to enhance children's polite behavior through a method focusing on five key